Fuel-Powered Soft Actuators: Emerging Strategies for Autonomous and Miniaturized Robots - Zhou, Cheng; Li, Zhoutao; Wei, Hailong; Zhang, Guorong; Zhang, Fengrui; Zhou, Xiaoshuang; Hu, Hongwei; Cheng, Guanggui; Ding, Jianning; Kim, Shi Hyeong; Baughman, Ray H.; Hu, Xinghao (Nano-Micro Letters, 2026)
Soft actuators, capable of producing mechanical work in response to external stimuli, have potential applications in robotics and exoskeletons. However, they face major challenges related to energy supply, especially in long-distance and miniaturized environments. Fuel-driven actuators offer a promising solution by enabling the conversion of chemical energy into mechanical energy, supporting self-sustaining operations. Chemical energy from fuel can be converted into mechanical energy either directly or indirectly through methods such as electron transfer-induced charge injection, structural changes, fuel-to-electricity conversion, fuel combustion-induced heat, or fuel-induced pneumatic actuation. This paper provides a comprehensive review of recent developments in fuel-powered actuators, covering their fundamental principles, advancements, and challenges. It concludes with an outlook for miniaturized and autonomous robots, highlighting the great potential of integrating fuel-powered actuators. Highlights: 1 Fuel-powered soft actuators are elucidated in terms of their high power densities, enabling robots to operate effectively in long-distance or miniaturized environments. 2 The working principles, applications, and potential future improvements of typical fuel-powered actuators are comprehensively reviewed and discussed 3 Existing challenges and the future pathways for fuel-powered soft robots are delineated.